Measuring the Amount of Effects of Capability Approach on Developing E-government - behroz Zarei; fatemeh Saghafi; lila Zarrin (Journal of Information Technology Management)
In capability approach (C.A.), the concepts of developed and undeveloped and their realization instruments are different from other common approaches. Just those who are provided with personal capabilities and environmental conditions can be the messengers of development. In this approach background of our country in planning is ignored and resolved the challenges of development in e- government.  So at first, main challenges in developing e-government are identified, then models of C.A. and factors affecting it are extracted and classified. Next, the amount of effects of human capabilities on different challenges of e-government is surveyed based on QFD and ranked regarding Shannon Entropy. The results showed in e-government developing, considering the capabilities of people along with different ideas of the government can be influential. The important capabilities are as follows: the ability to create a democratic, free environment in the information community, accessing to this information, the ability to learn the electronic knowledge and the ability to offer services with electronic quality and the ability to preserve one’s rights in an electronic environment.